A justiça em Emmanuel Levinas: uma análise do Terceiro - Dias, Jefferson Polidoro (2016)
The following study is of bibliographic nature and aims at understanding the concept of justice in Emmanuel Levinas. After developing the criticism of the concept of totality, demonstrating how certain character ontology hid trapping and control, as well as the idea of ethics of infinite responsibility for the Other (Totality and Infinity), Lévinas explores content secondarily treated in his early writings, but which is of huge significance in his thinking, the Third, ie, society and the State. This other way of thinking the State develops, for Leévinas, ethics and the construction of political subjectivity. So I intend to focus this research in the works Totality and Infinity and Otherwise than Being, to understand how, through political imagination, a free and open society is possible, not based on inflexibility, but in the opening to the Infinite.